2022
DOI: 10.3390/land11020231
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Analysis between Rural Population Change and Rural Construction Land Changes in China

Abstract: Developing countries account for about 86.5% of the world’s population and are experiencing rapid urbanization. Globally, the increase in the urban population is generally accompanied by the expansion of the latter and construction lands, as well as the reduction in the rural population and rural construction lands. However, with the rapid development of urbanization in China, the rural population has decreased, while the proportion of rural construction lands has increased, resulting in a significant waste of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…However, due to the stagnation of economic development in the Northeast Region, an obvious further upward trend of the overall urbanization level was not observed, and some cities (such as Shenyang, Dalian, Changchun, and Daqing), which originally had a relatively high level of overall urbanization, even appeared to undergo the phenomenon of "anti-urbanization". Zhang et al ( 2022) reached similar conclusions [46]. On the contrary, some cities (such as Dandong, Panjin, Jiamusi, and Harbin), which originally had a relatively low level of overall urbanization, show an improvement trend.…”
Section: Dynamic Changes In Urbanization Process In the Northeast Regionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, due to the stagnation of economic development in the Northeast Region, an obvious further upward trend of the overall urbanization level was not observed, and some cities (such as Shenyang, Dalian, Changchun, and Daqing), which originally had a relatively high level of overall urbanization, even appeared to undergo the phenomenon of "anti-urbanization". Zhang et al ( 2022) reached similar conclusions [46]. On the contrary, some cities (such as Dandong, Panjin, Jiamusi, and Harbin), which originally had a relatively low level of overall urbanization, show an improvement trend.…”
Section: Dynamic Changes In Urbanization Process In the Northeast Regionmentioning
confidence: 86%
“…We also selected a series of controlling variables, which can affect the agricultural technical efficiency. The existing research shows that the crop planting structure, agricultural mechanization, financial support for agriculture, and the degree of openness will all have impacts on the agricultural technical efficiency [45,46]. Therefore, we specifically selected the proportion of grain crops in the total sown area of crops (stru), the ratio of the total power of the agricultural machinery to the total sown area of crops (mac), the level of financial support for agriculture (agr), and the agricultural FDI (fdi) as the controlling variables.…”
Section: Controlling Variablesmentioning
confidence: 99%
“…It is vital in promoting coordinated regional development and participating in international cooperation and competition. However, there are still some problems in urban agglomerations in China, such as the uncoordinated development of cities and their factors and low efficiency of resource allocation (Fan et al, 2019;Ji et al, 2020;Lin et al, 2021;Zhang et al, 2022). The study of the economic agglomeration effect of population-land allometric growth found that the current rapid economic development in the YRD is still dominated by land expansion, consistent with the results analyzed by scholars using econometric models , and it also shows a time lag in the economic impact of population-land allometric growth between regions.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…Due to lack of planning, the idle use of the original homestead and the new demand for construction lands had caused the continuous expansion of rural construction lands(X. Zhang et al 2022). Under the lowcarbon scenario, the rural land is increasingly occupied by the surrounding urban construction land, demonstrating a shrinking trend.…”
Section: Land-use Capability Of Carbon Storage and Carbon Emissionmentioning
confidence: 99%